PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS KETERAMPILAN BEKERJASAMA DAN BERKOMUNIKASI MENGGUNAKAN MODEL LEARNING CYCLE (7E) PADA SUB POKOK BAHASAN OPERASI HIMPUNAN KELAS VII SMP - Lailiya, Muhimatul; Sunardi, Sunardi; Kurniati, Dian (Department of Mathematics Education , University of Jember, 2016)
The goal of this research is to know the process and the result of developmental mathematic learning instrument base on cooperative and communicative skills using learning cycle 7E model on sub topic set operation 7th grade of junior high school. Developmental learning instruments refers to Thiagarajan, Semmel, dan Semmel models. The product of this research are lesson plan, worksheet, and student book. The products refers to the learning cycle 7E model base on cooperative and communicative skills. The trial subject of this research is student of grade VIIA Mts. Al Ma'arif Wuluhan. Data collection technique in this research is validation, observation, student project and self assessment. Mathematic learning instruments developed has met validity, practice, and effective criteria.